AUTONOMY-SUPPORTIVE OR AUTONOMY-THWARTING: THE ROLE OF PARENTING PROFILE IN PREDICTING SELF-REGULATED LEARNING IN INDONESIAN UNIVERSITY STUDENTS: Autonomy-Supportive or Autonomy-Thwarting: Peran Profil Pengasuhan sebagai Prediktor Regulasi Diri dalam Belajar Mahasiswa Indonesia - Caroline Mathilda V. Bolang; Christina Claudia; Samuel Adiprasetya Isaputra (Faculty of Social Science and Human Ecology, IPB University, 2025)
For the past three decades, self-regulated learning (SRL) has been a key focus in educational psychology, with both parenting and teaching strategies playing crucial roles. This study aims to examine the role of Helicopter Parenting (HP) on Indonesian college students’ SRL.Sampling was conducted using a non-probability approach, specifically employing a convenience sampling technique. A survey method was used to measure the perceptions of 256 Indonesian college students regarding their parents’ parenting profiles using the Helicopter Parenting Instrument – Short Version (HPI-S) and their SRL using the Motivated Strategies for Learning Questionnaire (MSLQ). The results indicate that HP significantly contributes to the development of SRL among Indonesian college students. This finding contradicts most previous studies. However, further analysis suggests that a significant portion of SRL variability remains unexplained by HP and may be influenced by other factors. Culture emerges as a crucial factor deserving attention and is discussed as a key influence on the outcomes of this research.